Pharmacokinetics of Single Dose Lidocaine and Epinephrine Following Iontophoresis of the Tympanic Membrane in a Double-Blinded Randomized Trial - England, Laura J; Syms, 3rd, Charles A; York, Christopher (Otology & neurotology, 2021)
To evaluate local and systemic safety of bilateral iontophoretic administration of lidocaine with epinephrine or lidocaine alone to the tympanic membrane (TM). A randomized, double-blind, two-arm study was conducted at a single center. Healthy adults were randomized to bilateral iontophoretic treatment with 2% lidocaine, 1:100,000 epinephrine, or 2% lidocaine (control). Otoscopy, cranial nerve examination, tympanometry, and audiometry safety evaluations were conducted before and 3-days post-procedure. Systemic safety was evaluated via analysis of vital signs taken before and up to 120 minutes post-iontophoresis, and blood samples collected before and up to 230 minutes post-iontophoresis. Twenty-five subjects were treated with bilateral iontophoresis of either lidocaine and epinephrine (n = 15 subjects) or lidocaine alone (n = 10). Mean plasma epinephrine concentrations for both groups remained within the normal range for endogenous epinephrine. Mean plasma concentrations of lidocaine were not statistically different between groups, ranging from 0.245 to 2.28 ng/ml after administration of lidocaine with epinephrine (immediate post-iontophoresis to 230 min post-iontophoresis), compared with 1.35 to 2.14 ng/ml after administration of lidocaine alone. The presence of epinephrine slowed the systemic absorption of lidocaine. Lidocaine levels (Cmax 2.24 ng/ml) were approximately 2000-fold lower than the threshold for minor lidocaine toxicity. No device-, procedure- or drug-related adverse events were reported. The local and systemic safety of bilateral iontophoretic delivery of 2% lidocaine, 1:100,000 epinephrine to the TM was demonstrated by low plasma levels of drug and absence of both serious and non-serious device-, procedure-, or drug-related adverse events.